Haploid and mixoploid cucumber (Cucumis sativus L.) protoplasts – isolation and fusion (Journal of Applied Botany and Food Quality, 2012)
This paper reports on the isolation of haploid and mixoploid protoplasts in the genus Cucumis. The cucumber mixoploid plants (C. sativus L., 2x/4x; 2x = 14) were obtained after oryzalin treatments and the mesophyll protoplasts (2x/4x/8x) were isolated and cultivated by well known in vitro methods. The influence of oryzalin pretreatment on the average viability and density of  protoplasts was tested. The average viability as well as the density is signifi cantly influenced by the oryzalin concentration, whereas the time-span of the treatment doesn’t have significant impact on the density and the viability. Callus formation was the highest level of regeneration in the experiments described in our study. Furthermore the isolation and cultivation of the cucumber and muskmelon (C. melo L.; 2x = 24) haploid protoplasts from young-stage pollen grains were improved. Subsequently, somatic hybridization between mixoploid cucumber protoplasts and muskmelon mesophyll and callus protoplasts, and kiwano (C. metuliferus E. Meyer ex Naudin; 2x = 24) mesophyll protoplasts, by chemical fusion with polyethylene glycol (PEG) 6000 was performed for the first time. Heterofusants were observed and developed into micro colonies. Additionally, the gametosomatic hybridization between mixoploid cucumber protoplasts and pollen muskmelon protoplasts was performed for the first time. Heterofusants and the first cell division were observed, however, the regeneration stopped in this stage. In conclusion, the different ploidy, especially the mixoploid character of isolated protoplasts, has positive influence on protoplasts isolation and the following fusion as represented by a higher regeneration capacity. In addition, both types of protoplasts, haploid and mixoploid, represent a unique systems for biochemical, molecular and genetic experiments. Especially, the haploid protoplasts could be used during in vitro fertilization.